PERAN PEMERINTAH KABUPATEN SIMEULUE DALAM PEMBERDAYAAN AIR BERSIH DAN SANITASI GUNA MENDORONG PENGEMBANGAN KAPASITAS DAERAH SERTA PENYEDIAAN PELAYANAN AIR MINUM DAN PENYEHATAN LINGKUNGAN UNTUK MEMENUHI TARGET UNIVERSAL ACCES 100% MDGS PROGRAM TINGKAT NASIONAL - Alimas Jonsa; Irwan Suharmi (Jurnal Public Policy, 2018)
The role of the government in empowering the development community in the Simeulue Islands Regional Water Supply and Environmental Sanitation Action Plan (RAD) will not succeed if it is not balanced with a public awareness program that is an effort to reduce, poor culture by way of remind, convince and injections to the community. To be trying to bounce do the hard work to get used to shame the poor receive aid as well as mental block change. The program targets AMPL activities in sequential order from the district level, the District, the Village (Village / Agencies) reached the target group. This is done through a mechanism in the development plan Deliberation annual planning and budgeting cycle of the area. The purpose of RAD AMPL needs to be supported by the role of the government by prioritizing synergic relations between elements of government, the private sector and civil society and involving the community itself based on the principles of Vision Strategy, by means of transparency, participation, and responsibility, by prioritizing community interests. By looking at the conditions of the community above, the government needs to do a social empowerment. Thus the RAD AMPL requires the support and participation of all development actors from the government, DPRD, universities, organizations and non-governmental organizations, private and international institutions. The involvement of all development actors are expected to encourage the establishment of a common point of view, the agreement and synergy in the efforts to Accelerate Achievement of Universal Access target of 100%. Keywords: Role, Government, Empowerment, Clean Water